Lifestyle Factors and Parkinson's Disease Risk in a Rural New England Case-Control Study. (2nd July 2021) - Andrew, Angeline S.; Anderson, Faith L.; Lee, Stephen L.; Von Herrmann, Katharine M.; Havrda, Matthew C.
Abstract : Introduction . Parkinson's disease (PD) is an age-related neurodegenerative disease likely caused by complex interactions between genetic and environmental risk factors. Exposure to pesticides, toxic metals, solvents, and history of traumatic brain injury have been implicated as environmental risk factors for PD, underscoring the importance of identifying risk factors associated with PD across different communities. Methods . We conducted a questionnaire-based case-control study in a rural area on the New Hampshire/Vermont border, enrolling PD patients and age- and sex-matched controls from the general population between 2017 and 2020. We assessed frequent participation in a variety of recreational and occupational activities and surveyed potential chemical exposures. Results . Suffering from "head trauma or a concussion" prior to diagnosis was associated with a fourfold increased risk of PD. Adjustment for head trauma negated any risk of participation in "strenuous athletic activities." We observed a 2.7-fold increased risk of PD associated with activities involving lead (adjusted p = 0.038 ). Conclusion . Implicating these factors in PD risk favors public health efforts in exposure mitigation while also motivating future work mechanisms and intervention opportunities.